Assessment of learning outcomes : assessment 1 - Navarro, Rosita L.; Santos, Rosita G. (Quezon City, Philippines : Lorimar Publishing Company Inc., 2012)
The book Assessment of Learning Outcomes (Assessment 1 ) implements and complements OBE by clarifying the concept of Outcomes-Based Education (OBE) identifying and explaining student learning outcomes at the different levels of schooling, and illustrating a variety of assessment tools to determine if the desired are provided at the end of the chapter. every chapter of the book includes models and examples to aid students' understanding. To enhance their capability to apply the concept learned, and relevant exercises are provided at the end of the chapter.
Foreword -- Preface -- Shift of Educational Focus from Center to Learning Outcomes -- Measurement, Assessment and Evaluation in Outcomes-Based Education -- The Outcomes of Student Learning -- Assessing Student Learning Outcomes -- Developing Varied Assessment Tools -- Item Analysis and Validation -- Performance- Based Tests -- Grading Systems -- References -- Appendix A.
Includes bibliographical references.
Keywords: OUTCOMES AND COMPETENCY -- BASED LEARNING -- PHILIPPINES